Desain Sistem Penjualan Pada Juvara Food - Laurentius Rio Ageng Surya Susandy Rio; Ignatius Novianto Hariwibowo Novi; B. Subhashini; Ni Putu Ayu Utari Widiantini; Christina Nathasya Putri (Jurnal Atma Inovasia, 2025)
The Juvara Food Sales System is designed to make it easier for customers to find and order cooking spices online. This system is a solution for individuals who want to cook practically without having to mix their own spices. In addition, this system also supports restaurants in obtaining high-quality spices without additional ingredients such as MSG. This service aims to design a sales information system that can help Juvara Food. The development process includes needs analysis, web-based system design, and feasibility evaluation from economic aspects. The design is carried out using context diagrams, data flow diagrams (DFDs), and entity-relationship diagrams (ERDs) to ensure that the system can operate optimally. It is hoped that this system will be able to speed up the digital ordering and payment process as well as expand the target market, as well as provide a more convenient shopping experience for customers.